Preparation and Obstacle of Notary in Making Notarial Deed in Facing Society 5.0 Era - Yotia Jericho Urbanus; I Made Pria Dharsana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This writing discusses the preparation and obstacle of Notary in making Notarial deed in facing. Notary Deed is an authentic deed made by or before a Notary according to the form and procedure stipulated in Undang-Undang Number 2/2014. According to Article 1868 of the Civil Code, an authentic deed is a deed made in a form determined by law by or before a public official authorized for that purpose at the place where the deed was made. This gives an indication that a deed made by a Notary as a public official can be said to be an authentic deed if it meets the requirements as described in the article. The entry of society 5.0 era in Indonesian society causes the need for an adaptation for Notaries in Indonesia in terms of meeting the needs of people who are affiliated with technology, especially in making authentic deeds. Initially, the use of technology such as the use of video conferences, electronic signatures, electronic ID verification tools and the liveliness test system was considered the answer for Notaries in terms of meeting the community's need for authentic deeds, especially in dealing with technological developments that entered all aspects of human life. However, Indonesia as a legal state that has the spirit to always ensure justice and legal certainty, causes all actions taken by a legal subject to be guided by the law that governs it. In this case, there are obstacles in the use of video conferencing, electronic signatures, electronic ID verification tools and the liveliness test system due to the absence of a legal basis that serves as a legal umbrella for their use in making a notarial deed. Furthermore the concept of facing using technological developments cannot be equated with being physically present as described in Undang-Undang Jabatan Notaris.